ANALYSIS OF THE IMPACT OF CUSTOMER EXPERIENCE ON REPURCHASE ATTITUDES AND INTENT IN ONLINE GROCERY RETAIL: MODERATING FACTORS OF SHARED VALUE CREATION - Zaenal Aripin; Bambang Susanto; Nurhaeni Sikki (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
The rapid development of online grocery retailing demands a deep understanding of the factors that influence customer purchasing decisions. This research aims to analyze the impact of customer experience on attitudes and repurchase intentions in the context of online grocery retail, with an emphasis on the moderating factors of shared value creation. The primary objective of this research is to understand the extent to which customer experience can influence consumer attitudes and repurchase intentions in an online grocery retail environment. In addition, this research aims to identify the role of moderating factors of value co-creation in changing the dynamics of the relationship between customer experience, attitudes and repurchase intentions. The research method used is quantitative with a survey approach. The sample was randomly selected from the population of online grocery retail customers and analyzed using relevant statistical techniques. The research instrument involved a questionnaire designed to measure customer experience variables, consumer attitudes, repurchase intentions, and moderating factors of shared value creation. The research results show that customer experience has a significant positive impact on consumer attitudes and repurchase intentions. The moderating factor of value co-creation has also been shown to play an important role in strengthening the relationship between customer experience and consumer attitudes. These results provide a better understanding of the complex dynamics in customer purchasing decisions in the context of online grocery retailing.